2019
DOI: 10.3390/mps2010023
|View full text |Cite
|
Sign up to set email alerts
|

An Evidence-Based Objective Study Protocol for Evaluating Cardiovascular and Cerebrovascular Indices Following Concussion: The Neary Protocol

Abstract: Introduction: The prevalence and incidence of sport-related concussion have continued to increase over the past decade, and researchers from various backgrounds strive for evidenced-based clinical assessment and management. When diagnosing and managing a concussion, a battery of tests from several domains (e.g., symptom reporting, neurocognitive, physiology) must be used. In this study, we propose and develop an objective, evidence-based protocol to assess the pathophysiology of the brain by using non-invasive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 50 publications
1
20
0
Order By: Relevance
“…The 8-channel system (OctaMon, Artinis Medical, Netherlands) monitored changes in O 2 Hb and HHb in the pre-frontal cortex, specifically covering the dorsolateral (DLPFC) and orbitofrontal (OFC) cortices in both hemispheres (Vergotte et al, 2018). Our study performed a modified Neary Protocol (Neary et al, 2019) to assess NVC using the ''Where's Wally (Waldo)'' paradigm. Previous research has confirmed this test is a valid measure of NVC (Smirl et al, 2016).…”
Section: Fnirs Device and Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…The 8-channel system (OctaMon, Artinis Medical, Netherlands) monitored changes in O 2 Hb and HHb in the pre-frontal cortex, specifically covering the dorsolateral (DLPFC) and orbitofrontal (OFC) cortices in both hemispheres (Vergotte et al, 2018). Our study performed a modified Neary Protocol (Neary et al, 2019) to assess NVC using the ''Where's Wally (Waldo)'' paradigm. Previous research has confirmed this test is a valid measure of NVC (Smirl et al, 2016).…”
Section: Fnirs Device and Protocolmentioning
confidence: 99%
“…The researchers did not communicate with the participant during this baseline data collection period. The ''Where's Wally'' test (Smirl et al, 2016;Neary et al, 2019) was then implemented on a plasma screen (42" size), with the participant sitting 180 cm away. Each of the five cycles (5 min in total) consisted of 20 s of eyes closed followed by 40 s of eyes open where the participant searched the screen for ''Wally.''…”
Section: Fnirs Device and Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…If the participants had baseline data collected first, a within-subject design based on this effect size will require 29 participants per group to demonstrate significance. This demonstrates the importance of including baseline testing in sport-related concussion research which has been documented previously (Len et al, 2013;Neary et al, 2019).…”
Section: Comparison Of Nirs Hemodynamics Between Control Vs Mtbi Parmentioning
confidence: 61%
“…Most recently, exertional exercise testing protocols, such as the Buffalo Concussion Treadmill and Bike Test have proven to be safe and efficacious (Leddy et al, 2016aHaider et al, 2019;Morissette et al, 2019) in evaluating the athletes post-concussion. These laboratory testing protocols have been designed with the intent to differentiate the type of concussion injury (i.e., physiologic, vestibulo-occular, cervicogenic;Ellis et al, 2014Ellis et al, , 2015Leddy et al, 2016a), and to discern the physiological mechanisms (cerebral autoregulation, cerebrovascular reactivity, neurovascular coupling; Ellis et al, 2015Ellis et al, , 2016Ellis et al, , 2018Neary et al, 2019). This research has added to our understanding of the pathophysiological changes that occur following a concussion (Len et al, 2011(Len et al, , 2013Giza and Hovda, 2014;Bishop and Neary, 2017;Bishop et al, 2017b;Worts et al, 2019), and has also provided a greater understanding of how we can apply exercise safely as a treatment strategy.…”
Section: Introductionmentioning
confidence: 99%